Subsídios ao extrativismo de briófitas no município de Cananéia, SP - Rancura, Sheila Aparecida de Oliveira (2009)
The management of non-timber forest products is an important alternative to forests maintenance. Nevertheless, the demand for some species at commercial scale may result in negative impacts to the local biodiversity. The bryophytes, particularly species of Sphagnum and Syrrhopodon genera, are among the vegetal resources exploited in restinga areas of Cananéia, in the south coast of São Paulo State, Brazil. After the organization of the harvesters in an association, the extraction is now legally carried out in licensed areas. The harvesting of bryophytes by the local population aims to supply the ornamental plants market, but there is a lack of studies to estimate the impact of the exploration providing information to the proper management of these resources. In order to provide subsidies for extraction and management of bryophytes Sphagnum and Syrrhopodon, this study raised information about the abundance and distribution of the explored bryophytes as well as the havesting practiced in Cananéia. To cover the different aspects involved in the harvesting of bryophytes, this study used Plant Ecology, Human Ecology and Ethnoecology approaches. Information concerning to the harvesters population and the harvesting activity were obtained through informal conversations, interviews and guided tours. Geoprocessing tools were used to characterize the bryophytes exploitation areas. The percentage ground cover by bryophytes was estimated applying the line-transect method and to evaluate the regeneration of Sphagnum plots were established and effected two harvests simulating traditional harvesting. The results indicated that explored bryophytes occur predominantly in Brejo de Restinga and Floresta Baixa de Restinga areas. Under similar conditions to those found in the experiment which simulated the traditional harvesting, the report demonstrated that six and seven months after harvest, Sphagnum presented height and yield like to the initial condition. In this sense, the harvesting, when done under the traditional way, tends to minimize the negative impacts of harvesting on the regeneration of bryophytes. Therefore, the relations determined in the commercialization process define the pressure upon exploited species and induces the harvesters to modify the traditional harvesting, resulting in an overexploitation of some places and a collect of very small bryophytes. Such actions contribute to a lower yield of the collect and may compromise the natural regeneration of some regions. The definition of management rules coupled to the bryophytes market rules built collectively constitute an essential point to established a less predatory harvesting.